„Listy, które czyta wielu”. Pseudokorespondencja św. Pawła z Seneką - Szarmach, Marian (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The apocryphal correspondence between St. Paul and Seneca, that is hardly touched upon in the scholarly literature, is an interesting example of a Christian „epistolographical novel” composed by poorly trained rhetorician.
„Letters read by many”. The apocryphal correspondence between St. Paul and Seneca
Keywords: St. Paul; Seneca; epistographical novel